Synthesis, In Vitro Antioxidant Properties and Distribution of a New Cyanothiophene-Based Phenolic Compound in Olive Oil-In-Water Emulsions - Sonia Losada-Barreiro; Matej Sova; Janez Mravljak; Luciano Saso; Carlos Bravo-Díaz (MDPI AG, 2020)
We synthesized and determined the antioxidant activity and distribution of a new cyanothiophene-based compound, N-(3-cyano-4,5,6,7-tetrahydrobenzo[b]thiophen-2-yl)-3,5-dihydroxybenzamide (SIM-53B), in intact stripped olive oil-in-water emulsion. The in vitro antioxidant properties of SIM-53B were evaluated and compared to those for Trolox and resveratrol. Addition of an emulsifier (Tween 20) creates a narrow region, the aqueous-oil interface, and the distribution of SIM-53B can be described by two partition constants: PWI (between aqueous/interfacial regions) and POI (between oil/interfacial regions). The effects of emulsifier concentration expressed in terms of the volume fraction, ΦI, and O/W ratio were also evaluated on its distribution. SIM-53B is predominantly distributed (>90%) in the interfacial region of 1:9 (O/W) olive oil-in-water emulsions at the lowest emulsifier volume fraction (ΦI = 0.005) and only a small fraction is located in the aqueous (<5%) and the oil (<5%) regions. Besides, the concentration of SIM-53B in the interfacial region of the emulsions is ~170-190-fold higher than the stoichiometric concentration, emphasizing the compartmentalization effects. Results suggest that the emulsifier volume fraction is a key parameter that may modulate significantly its concentration in the interface. Our study suggests that cyanothiophene-based compounds may be interesting additives for potential lipid protection in biomembranes or other lipid-based systems.